2011
DOI: 10.1016/j.lfs.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Important role of neutrophils in the late asthmatic response in mice

Abstract: Aims Neutrophils have been found increasingly in the lungs of patients with severe asthma; however, it is unclear whether the neutrophils contribute to the induction of the airway obstruction. We determined using a murine model whether neutrophils are involved in the late asthmatic response (LAR), and analyzed mechanisms underlying the antigen-induced airway neutrophilia. Main methods BALB/c mice sensitized by ovalbumin (OVA)+Al(OH)3 were challenged 4 times by intratracheal administration of OVA. Airway mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 47 publications
(70 reference statements)
4
44
0
Order By: Relevance
“…When examining the roles of neutrophils in various diseases, the anti-Gr-1 mAb, RB6-8C5, has been extensively used as a tool for depleting the granulocytes in mice (52)(53)(54). We have also demonstrated that depletion of neutrophils by the anti-Gr-1 mAb greatly suppressed a late-phase increase in airway resistance in actively sensitized mice (29). In this study, treatment with the anti-Gr-1 mAb before the fourth challenge significantly suppressed late-phase increase in both airway resistance and AHR under conditions of a marked reduction in the airway neutrophil count (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…When examining the roles of neutrophils in various diseases, the anti-Gr-1 mAb, RB6-8C5, has been extensively used as a tool for depleting the granulocytes in mice (52)(53)(54). We have also demonstrated that depletion of neutrophils by the anti-Gr-1 mAb greatly suppressed a late-phase increase in airway resistance in actively sensitized mice (29). In this study, treatment with the anti-Gr-1 mAb before the fourth challenge significantly suppressed late-phase increase in both airway resistance and AHR under conditions of a marked reduction in the airway neutrophil count (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The anti-CD4 mAb was produced and purified as described previously (28,29). The purified anti-CD4 mAb or rat IgG2b (eBioscience, San Diego, CA) was i.p.…”
Section: Treatment With Mabs or A C3a Receptor Antagonistmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, CD4 + cells and eosinophils had accumulated in the lung by the 1st -3rd challenges. In contrast, neutrophils increased before and after the 2nd -3rd challenges, returning to the circulation until before the 4th challenge (13,22). The 4th challenge caused the recurrence of neutrophilia at 4 h after the 4th challenge (Fig.…”
Section: Development Of Airway Cellular Infiltration and Lar And Effmentioning
confidence: 92%